A concise infertility work-up results in fewer pregnancies. Issue 4 (20th August 2021) - Hamilton, J A M; van der Steeg, J W; Hamilton, C J C M; de Bruin, J P
Abstract: STUDY QUESTION: Is pregnancy success rate after a concise infertility work-up the same as pregnancy success rate after the traditional extensive infertility work-up? SUMMARY ANSWER: The ongoing pregnancy rate within a follow-up of 1 year after a concise infertility work-up is significantly lower than the pregnancy success rate after the traditional and extensive infertility work-up. WHAT IS KNOWN ALREADY: Based on cost-effectiveness studies, which have mainly focused on diagnosis, infertility work-up has become less comprehensive. Many centres have even adopted a one-stop approach to their infertility work-up. STUDY DESIGN, SIZE, DURATION: We performed a historically controlled cohort study. In 2012 and 2013 all new infertile couples (n = 795) underwent an extensive infertility work-up (group A). In 2014 and 2015, all new infertile couples (n = 752) underwent a concise infertility work-up (group B). The follow-up period was 1 year for both groups. Complete follow-up was available for 99.0% of couples in group A and 97.5% in group B. PARTICIPANTS/MATERIALS, SETTING, METHODS: The extensive infertility work-up consisted of history taking, a gynaecological ultrasound scan, semen analysis, ultrasonographic cycle monitoring, a timed postcoital test, a timed progesterone and chlamydia antibody titre. A hysterosalpingography (HSG) was advised routinely. The concise infertility work-up was mainly based on history taking, a gynaecological ultrasound scan and semen analysis. A HSG was only performed if tubal pathology was suspected or before the start of IUI. Laparoscopy and hormonal tests were only performed if indicated. Couples were treated according to the diagnosis with either expectant management (if the Hunault prognostic score was >30%), ovulation induction (in case of ovulation disorders), IUI in natural cycles (in case of cervical factor), IUI in stimulated cycles (if the Hunault prognostic score was <30%) or IVF/ICSI (in case of tubal factor, advanced female age, severe male factor and if other treatments remained unsuccessful). The primary outcomes were time to pregnancy and the ongoing pregnancy rates in both groups. The secondary outcomes were the number of investigations, the distribution of diagnoses made, the first treatment (started) after infertility work-up and the mode of conception. MAIN RESULTS AND THE ROLE OF CHANCE: The descriptive data, such as age, duration of infertility, type of infertility and lifestyle habits, in both groups were comparable. In group A, more than twice the number of infertility investigations were performed, compared to group B. An HSG was made less frequently in group B (33% versus 42%) and at a later stage. A Kaplan–Meier curve shows a shorter time to pregnancy in group A. Also, a significantly higher overall ongoing pregnancy rate within a follow-up of 1 year was found in group A (58.7% versus 46.8%, respectively, P < 0.001). In group A, more couples conceived during the infertility work-up (14.7% versus 6.5%, respectively, P < 0.05). The diagnosis cervical infertility could only be made in group A (9.3%). The diagnosis unexplained infertility differed between groups, at 23.5% in group A and 32.2% in group B ( P < 0.001). LIMITATIONS, REASONS FOR CAUTION: This was a historically controlled cohort study; introduction of bias cannot be ruled out. The follow-up rate was similar in the two groups and therefore could not explain the differences in pregnancy rate. WIDER IMPLICATIONS OF THE FINDINGS: Re-introduction of an extensive infertility work-up should be considered as it may lead to higher ongoing pregnancy rates within a year. The therapeutic effects of HSG and timing of intercourse may improve the fertility chance. This finding should be verified in a randomized controlled trial. STUDY FUNDING/COMPETING INTEREST(S): No funding was obtained for this study. No conflicts of interest were declared. TRIAL REGISTRATION NUMBER: N/A.